Causes of Death Mother and Efforts to Reduce Mother Death Numbers in Luwu District, South Sulawesi Province - Erni1 , Muhammad Syafar2 , Irwandy3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study aims to analyze the indirect causes of maternal death. This type of research is qualitative with acase study approach. Data collection was carried out by document search, community visits, and interviews.The results showed that the total number of maternal deaths in Luwu district totaled 19 were spread across 13sub-districts, and maternal deaths generally occurred during labor and the puerperium. The indirect causesof maternal death can be seen from the close and far determinants. The close determinants were reviewedfrom three too late and four too, infectious diseases, far more determinant nutritional status in terms ofdistance, and the presence of obstetricians in obstetric emergencies. Efforts to reduce maternal mortality arethe main focus on the prevention of complications, immediately make referrals when maternal conditionsare still optimal. Empowering mothers and families.